Unveiling the molecular landscape of δ-thalassemia and δ-globin variants in southern China: novel mutations, gene spectrum, and implications for thalassemia diagnosis - Li, Youqiong; Ye, Lihua; Liang, Liang; Zheng, Lihong; Xiao, Yongjun; Lao, Zhongchan; Bai, Jinping; He, Xi; Fang, Qixun; Qin, Ting (Frontiers in Genetics, 2025)
Objectivesδ-thalassemia and δ-globin variants are rare hemoglobinopathies. However, co-inheritance of β-thalassemia and δ-globin gene mutations may affect the diagnosis of β-thalassemia carriers when based on the elevated Hb A2. This study aimed to identify and characterize δ-thalassemia and δ-globin variants in Southern China.MethodsNinety samples with suspected δ-globin gene mutations from 15,642 participants were selected for further molecular analysis based on their Hb A2 level (≦1.8%) and hematological parameters. Additionally, 37 samples with suspected δ-globin gene mutations were sent from other hospital to our laboratory for identification. GAP-PCR and PCR-reverse dot blot (PCR-RDB) were used to detect common α- and β-thalassemia in the Chinese population, and Sanger sequencing was used to identify δ-globin gene mutations.ResultsAmong 15,642 samples examined, samples with δ-globin gene mutations were identified in 127 (0.81%) cases with as many as 28 different genotypes, including 81 (0.52%) cases of δ-thalassemia and 46 (0.29%) cases of δ-globin variants. The most prevalent δ-thalassemia and δ-globin variants of this study were HBD:c.−127T>C (75.3%, 61/81) and Hb A2-Melbourne (54.3%, 25/46). Most of the samples were heterozygous (87.4%, 111/127), and only two cases of homozygous were detected. There were three double heterozygotes and 11 cases of combined α/β-globin mutations. Notably, we also identified eight cases of novel mutations in the δ-globin gene. In both heterozygous and homozygous cases, δ-globin mutations maintained hematological parameters within normal ranges, while their co-occurrence with α- or β-thalassemia manifested as a thalassemia phenotype characterized by significantly reduced MCV and MCH values.ConclusionThe study reveals that δ-globin gene mutations are prevalence in the South China and necessitates integration of δ-globin screening into existing thalassemia prevention protocols.